Aldosterone and arterial hypertension - Tomaschitz, Andreas; Pilz, Stefan; Ritz, Eberhard; Obermayer-Pietsch, Barbara; Pieber, Thomas R. (Nature reviews. Endocrinology, 2010)
Raised levels of aldosterone, but also concentrations within the normal range are associated with elevated blood pressure. The authors of this Review assess evidence for the role of aldosterone in the development and maintenance of hypertension, including experimental and clinical studies, and discuss the genetic and environmental mechanisms that underlie its effects.
Erstmals am 22. Dezember 2009 online veröffentlicht
Gesehen am 28.11.2023